Interactive Activities for Improving EFL Students' Speaking Skills - Ariqoh Nurjihan; Masayu Tya Salsabiela; Ali Al Faatih (English Education : English Journal for Teaching and Learning, 2026)
Although speaking is an important skill in English learning, many EFL students still struggle to express their ideas because of limited vocabulary and low confidence. This study aimed to develop and implement interactive learning media to support students’ speaking skills and classroom engagement. The study employed a Research and Development (R&D) approach using the ASSURE instructional design model. The media focused on the topic Describing Physical Appearance and was implemented in a tenth-grade class consisting of 21 students at an Islamic senior high school in Malang. Data were collected through classroom observations, interviews, documentation, and student response questionnaires. During the implementation, most students participated actively in the activities and were willing to take part in classroom discussions. They were more confident in speaking English and interacted more often with their classmates. Students also gave positive responses to the activities and were more willing to use English during classroom interactions. Overall, the results suggest that the use of ASSURE-based interactive media helped students practice speaking more actively and made the learning process more engaging.